Placental Localisation with 99mTc-Labelled Red Blood Cells - Singh, P. M.; Rehani, M. M.; Devi, P. K. (Nuklearmedizin - NuclearMedicine, 1980)
The accuracy of placental localisation by radioisotopic scanning using 99mTc-labelled red blood cells has been estimated in 20 patients. The results have been correlated with the findings at delivery by direct and indirect methods. The accuracy of results regarding upper and lower segment insertion of the placenta was 90 % in the present study.